Myocardial fibrosis predicts ventricular arrhythmias and sudden death after cardiac electronic device implantation. (19th May 2022) - Zegard, A; Okafor, O; Foley, P; Umar, F; Taylor, R; Marshall, H; Stegemann, B; Moody, W; Steeds, R; Halliday, B; Hammersley, D; Jones, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Unrestricted educational grants Background: Increasing evidence supports a link between myocardial fibrosis (MF) and ventricular arrhythmias. We sought to determine whether presence of MF on visual assessment (MFVA) and gray zone fibrosis (GZF) mass predicts SCD and ventricular fibrillation / sustained ventricular tachycardia after cardiac implantable electronic device (CIED) implantation. Methods: In this prospective study, total fibrosis and GZF mass, quantified using cardiovascular magnetic resonance, was assessed in relation to the primary endpoint of sudden cardiac death (SCD) and the secondary, arrhythmic endpoint of SCD or ventricular arrhythmias after CIED implantation. Results: Among 700 patients (age 68.0 ± 12.0yrs [mean ± SD]), 27 (3.85%) experienced a SCD and 121 (17.3%) met the arrhythmic endpoint over 6.93 yrs (median; interquartile range 5.82-9.32). MFVA predicted SCD (hazard ratio [HR]: HR:26.3 [95% confidence interval [CI] 3.70-3337]; negative predictive value: 100%). In competing risks analyses, MFVA also predicted the arrhythmic endpoint (subdistribution [sHR]: 19.9 [95% CI 6.40-61.9]; negative predictive value:98.6%). Compared with no MFVA, a GZF mass measured with the 5SD method (GZF5SD) > 17 g was associated with highest risk of SCD (HR: 44.6;95% CI 6.12-5685) and the arrhythmic endpoint (sHR: 30.3 [95% CI 9.60-95.8]). Adding GZF5SD mass to MFVA led to reclassification of 39% for SCD and 50.2% for the arrhythmic endpoint. In contrast, LVEF did not predict either endpoint. Conclusions: In CIED recipients, MFVA excluded patients at risk of SCD and virtually excluded ventricular arrhythmias. Quantified GZF5SD mass added predictive value in relation to SCD and the arrhythmic endpoint.